Who votes for mayor? Evidence from midsized American cities. Issue 4 (4th July 2019) - Aldag, Austin M.
ABSTRACT: Who, or what, governs the mosaic of the almost 39, 000 general purpose local governments across the United States? While the determinants of voter turnout in both national and sub-national elections have been well studied, there is a dearth of empirical literature examining voter turnout at the municipal level. Utilizing an original dataset of 356 midsized US cities drawn from the Midwest, South, and Northeast regions, this paper ponders the drivers of mayoral turnout, and asks if electoral timing, competitiveness, or characteristics of the electorate best predict turnout. Sequenced hierarchical linear models and OLS regressions are employed to control for sub-national effects, and model results indicate that election timing greatly dictate who governs midsized American cities. While local competitiveness and characteristics of the electorate also matter, their explanatory value is greatly over-shadowed by timing.